Parental role in supporting inclusive education for children with autism - Tsaputra, Antoni; Muliadi; Rahmahtrisilvia; Nurhastuti; Amani, Risca (Indonesian Journal of Educational Development (IJED), 2025)
This research examines the role of parents in supporting the education of children with autism in special schools in Langsa City, Aceh. With the increasing number of children with autism spectrum disorders, attention to their educational needs has become very important. This research aims to identify the various roles played by parents and analyze the impact of their support on the social and academic development of the child. Qualitative descriptive methods were employed to assess the impact of parental involvement in the educational process on children's learning outcomes and social interactions. Data was collected using purposive sampling techniques. Data collection techniques used observation, interviews, and document studies, with the instruments used being observation guidelines and interview guidelines. The research results show that parents function as the primary supporters, who not only provide motivation but also play a crucial role in communication with teachers and in monitoring their child's development. Parental support has been proven to enhance children's self-confidence and social skills, thereby creating a more inclusive learning environment. Involving parents in the planning and evaluation of educational programs can significantly improve children's learning outcomes.